Improving health care provider - health committee working relationships for responsive, people-centred health systems - Zwama, Gimenne (Department of Public Health and Family Medicine, 2017)
As community-based governance structures in the service delivery of primary health care, health committees can promote the quality, accessibility and responsiveness of service delivery. More specifically, health committees provide a platform for community members to advocate for their health needs and meaningfully participate in decision-making, oversight and monitoring of service delivery. Hence, health committees provide a bottom-up strategy to realise the right to health and a people-centred health system. Previous research has found that Health Committees in the Cape Metropole of South Africa face similar challenges as their counterparts globally. In South Africa health committees' role and mandate often seem to be unclear and weak policy frameworks have resulted in wide variations in health committee functionality. Health care providers, particularly health facility managers, have been identified to play a key role in creating a supportive environment for health committees' genuine and effective participation. Particularly, health care providers' misunderstandings of health committees' roles and responsibilities as well as their lack of engagement with health committees can form barriers to health committee's functioning. A gap in understanding exists on the impact training of health care providers could have on health committees' meaningful participation. While many health committee members in the Cape Metropole of the Western Cape Province were already trained, health care providers had not been trained until May 2015. Present realist evaluation sought to describe and explore the immediate and short-term impact of this pilot training on health care providers' responsiveness towards health committees. Pre- and post-training questionnaires, direct observations and semi-structured interviews were employed as research methods. The training evaluation was enriched by participants' diverse professional positions and work environments as well as their various experiences and relationships with health committees. The study reveals that the training played a role in increasing health care providers' responsiveness towards health committees' roles and functions. Health care providers demonstrated understandings and intentions towards building effective working relationships with health committees. However, training is recommended to be followed up on and to be continuous to ensure intentions are translated into practice and to account for the dynamic nature of health facilities, health committees and the health system in which they reside. In this manner, health care providers can increasingly contribute to building sustainable relationships with health committees to promote meaningful and effective community participation, the strengthening of people-centred health systems and the progressive realisation of the right to health.